SOSIALISASI SANITASI DAN KEAMANAN PANGAN SERTA SISTEM JAMINAN HALAL PRODUK YOGHURT DAN NATA DE COCO PADA UMKM YOSUKA DAIRY - Badriansyah, Liska; Azizah, Liza Shinta Nur; Ferlincha, Kiki Nola; Lestari, Dede Amara; Fauziah, Ratu Dwi; Pravitri, Nabila Feby; Syifa, Nurhaeni; Novidahlia, Noli (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2022)
Usaha Mikro, Kecil dan Menengah (UMKM) are one of the business sectors that are required to compete by creating products that are acceptable to consumers. In Indonesia, the growth of UMKM is increasing from year to year, so the development of UMKM will be very strategic to move or improve the national economy. In addition, UMKM are also able to improve specific strategies to create unique products that can compete with products from businesses whose names have soared. This is because MSMEs are able to increase creativity which is in line with efforts to maintain and develop elements of the traditions and culture of the local community. Kuliah Kerja Nyata (KKN) is one of the methods used to develop students' potential by devoting themselves directly to the community. Meanwhile, KKN held in an UMKM can be carried out to develop potential by empowering students participating in KKN. Keyword: UMKM, KKN, Devotion, sanitation, halal assurance system